PELATIHAN DIGITALISASI PERIZINAN USAHA (OSS RBA) UNTUK MENCIPTAKAN KEMANDIRIAN EKONOMI BAGI MAHASISWA MELALUI USAHA JASA - Baiq Dinna Widiyasti; Zahrah Zahrah; RR Prima Dita Hapsari; L Jatmiko Jati (Jurnal Abdi Insani, 2026)
NTB's potential to become a province with a high economy, still has to be risked by the unemployment rate it has. The government is encouraging the creation of 5,000 new MSMEs, not followed by the legality of their businesses, considering that our government has facilitated the process with digitalization and independence. Therefore, this community service activity is felt necessary to seek opportunities to reduce the number of unemployment that can arise from graduates through improving soft skills that are also able to address the current need for business legality that is not comparable to the number of existing businesses. This service is carried out through the methods of observation, preparation and planning, training and implementation. With the results being able to increase the skills of Gen Z who have a close relationship with digitalization, it becomes a solution in helping MSMEs carry out business legality to provide an independent economy for students through these service businesses, so that it is hoped that in the future regional economic problems can be resolved.